Cranial and large vessel activity on positron emission tomography scan at diagnosis and 6 months in giant cell arteritis. (26th February 2020) - Sammel, Anthony M.; Hsiao, Edward; Schembri, Geoffrey; Bailey, Elizabeth; Nguyen, Katherine; Brewer, Janice; Schrieber, Leslie; Janssen, Beatrice; Youssef, Peter; Fraser, Clare L.; Laurent, Rodger
Abstract: Aim: Positron emission tomography/computed tomography (PET/CT) can detect cranial and large vessel inflammation in giant cell arteritis (GCA). We aimed to determine the change and significance of vascular activity at diagnosis and 6 months. Method: Newly diagnosed GCA patients underwent time‐of‐flight fluorine‐18‐fluoro‐2‐deoxyglucose PET/CT from vertex to diaphragm within 72 hours of commencing corticosteroids and were followed for 12 months. A 6 months scan was performed in patients with inflammatory features on biopsy or CT aortitis. Vascular uptake was visually graded by 2 blinded readers across 18 artery segments from 0 (no increased uptake) to 3 (very marked uptake). Scores were summed to give a total vascular score (TVS). Results: We enrolled 21 GCA patients and 15 underwent the serial scan. Twelve (57%) patients experienced a relapse and 5 of these had ischemic features of vision disturbance, jaw or limb claudication. The median TVS fell from 14 (interquartile range [IQR] 4‐24) at baseline to 5 (IQR 0‐10) at 6 months ( P < .01) with reduction in both cranial and large artery scores. While the overall relapse rate was similar between patients with a high (≥10) and low baseline TVS, patients with high scores were numerically more likely to experience an ischemic relapse (33% vs 11%, P = .34). Five out of 15 patients had persistent uptake in at least 1 vessel on the serial PET/CT but none experienced a subsequent relapse. Conclusion: Vascular activity decreased in cranial and large arteries between diagnosis and 6 months. Persistent activity did not predict subsequent relapse.